2021
DOI: 10.1111/jcmm.17142
|View full text |Cite
|
Sign up to set email alerts
|

The role of Cold‐Inducible RNA‐binding protein in respiratory diseases

Abstract: Cold‐inducible RNA‐binding protein (CIRP) is a stress‐response protein that is expressed in various types of cells and acts as an RNA chaperone, modifying the stability of its targeted mRNA. Intracellular CIRP could also be released into extracellular space and once released, extracellular CIRP (eCIRP) acts as a damage‐associated molecular pattern (DAMP) to induce and amplify inflammation. Recent studies have found that eCIRP could promote acute lung injury (ALI) via activation of macrophages, neutrophils, pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Recent studies have epitomized that eCIRP can promote acute lung injury via activation of macrophages, neutrophils, pneumocytes, and lung vascular endothelial cells in the context of sepsis, hemorrhagic shock, intestinal ischemia/reperfusion injury, and severe acute pancreatitis. 19 Macrophage erythropoietin receptor signaling is impaired by eCIRP through Rab26 during acute lung injury/acute respiratory distress syndrome, leading to restrained M2 macrophage polarization and delayed resolution of inflammation. 20 Furthermore, eCIRP dysregulates macrophage bacterial phagocytosis during sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have epitomized that eCIRP can promote acute lung injury via activation of macrophages, neutrophils, pneumocytes, and lung vascular endothelial cells in the context of sepsis, hemorrhagic shock, intestinal ischemia/reperfusion injury, and severe acute pancreatitis. 19 Macrophage erythropoietin receptor signaling is impaired by eCIRP through Rab26 during acute lung injury/acute respiratory distress syndrome, leading to restrained M2 macrophage polarization and delayed resolution of inflammation. 20 Furthermore, eCIRP dysregulates macrophage bacterial phagocytosis during sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…There are two different forms of CIRP: intracellular CIRP and eCIRP. Currently, increasing evidence has indicated that eCIRP is critically involved in the development of inflammatory diseases [ 13 , 14 ]. It is likely that eCIRP is associated with alcohol-, haemorrhage- and cerebral ischaemia-induced brain inflammation [ 15–18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an endogenous in ammatory factor, CIRP directly induces the upregulation of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and other pro-in ammatory cytokines in serum, thereby initiating a cascade reaction of in ammation and exacerbating tissue injury [12,13]. Recent studies have indicated the involvement of CIRP in the pathogenesis of various respiratory diseases, including chronic obstructive pulmonary disease (COPD), idiopathic pulmonary brosis (IPF), and acute respiratory distress syndrome (ARDS)/ acute lung injury (ALI) [14,15]. The expression of CIRP is signi cantly elevated in bronchial epithelial cells, both in patients with chronic obstructive pulmonary diseases (COPD) and in rat models with chronic bronchitis [16].…”
Section: Introductionmentioning
confidence: 99%